Ruth Kelso, Doctrine for the lady of the Renaissance. University of Illinois Press, Urbana, 1956; xi + 475 pp. - Vergara, M. A. (El Colegio de México, 1960)
Se reseñó el libro: Doctrine for the lady of the Renaissance.